Deep diving by offshore bottlenose dolphins ( Tursiops spp.) - Andreas Fahlman; Reny B. Tyson Moore; Rae Stone; Jay Sweeney; Robyn Faulkner Trainor; Aaron A. Barleycorn; Katherine McHugh; Jason B. Allen; Randall S. Wells (Marine Mammal Science, 2023)
We used satellite‐linked tags to evaluate dive behavior in offshore bottlenose dolphins ( Tursiops spp.) near the island of Bermuda. The data provide evidence that bottlenose dolphins commonly perform both long (>272 s) and deep (>199 m) dives, with the deepest and longest dives being to 1,000 m and 826 s (13.8 min), respectively. The data show a relationship between dive duration and dive depth for dives longer than about 272 s. There was a diurnal pattern to dive behavior, with most dives deeper than 50 m being performed at night; deep diving began at sunset and varied throughout the night. We used the cumulative frequency of dive duration to estimate a behavioral aerobic dive limit (bADL) of around 560–666 s (9.3–11.1 min) in adult dolphins in this population. Dives exceeding the bADL spent significantly longer time in the upper‐most 50 m following a dive as compared with dives less than the bADL. We conclude that the offshore ecotype off Bermuda, unlike the shallow‐diving near‐shore bottlenose dolphin, is a deep‐diving ecotype, and may provide a useful animal model to study extreme diving behavior and adaptations.